WAYS TO SOLVE THE DEVELOPMENT OF ECOTOURISM IN UZBEKISTAN (Academia Science Repository, 2023)
The article points out that ecotourism is one of the areas with great potential in Uzbekistan. But today, compared with other types of tourism, the share of ecotourism in the field is very small. Uzbekistan is not only famous for its historical monuments and architecture, but also has the opportunity to attract tourists with its unique natural habitats.